KINETIC ADSORPTION MODELING OF PHARMACEUTICALS ON ACTIVATED CARBONS - Корж, Е. А.; Клименко, Н. А. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2018)
Biologically active substances of pharmaceutical chemicals are considered as ew environmental contaminants. They exhibit biological activity even at microconcentrations, especially during the interaction with each other. Therefore, it leads to a practical need of actually complete removal of pharmaceutical substances (PS) from aqueous solutions. The adsorption capacity of activated carbons (AC) and the necessary contact time are two key indicators, which are determined by the adsorption equilibrium and the kinetics of adsorption. Static adsorption can only predict the final equilibrium state of the system. Kinetic analysis allows us to determine the adsorbate uptake rate and the time required for the completion of the adsorption process. Thus, the use of kinetic models for describing sorption processes of PS extraction from diluted aqueous solutions can allow us to characterize the mechanism of PS sorption on AC with different porous structure and establish the limiting adsorption stage for subsequent determination of rational conditions of implementing the water treatment process. Adsorption methods are important for the micropollutant extraction from aqueous systems and may be used for this purpose Applicability of mathematical models for kinetic adsorption regularities estimation of sulfanilamide, sulfathiazole, levamisole, procaine and caffeine on active carbons with different porous structure was analyzed. Adequacy of diffusion models of Boyd and Morris-Weber in the initial area (up to F ÷ 0,4-0,6) kinetic curves was shown. The effective diffusion coefficients and adsorption rate constants of reviewed kinetic models increased in the series levamisole < sulfathiazole < procaine < sulfanilamide < caffeine. Pseudo-second order model reflects the adsorption regularities most accurately.